Strategies for the Development of Sustainable Tourism Potential in Puncak Dunu, North Gorontalo - Desi Anggriani; Nurbaeti; Sri Mariati (CV. Science Tech Group, 2026)
Puncak Dunu nature tourism in North Gorontalo Regency has strong potential for local economic development but has not been managed optimally or sustainably. This study aims to analyze destination conditions based on the 5A components, examine tourists' perceptions, and formulate sustainable development strategies. A mixed-methods approach was applied using field observations, questionnaires to 100 respondents, and in-depth interviews with key stakeholders. The results show that natural attractions and special-interest activities are the main strengths, while amenities, accessibility, and ancillary services remain limited. Tourist perceptions are generally positive, yet revisit intention is low, with 52 percent of visitors visiting only once. SWOT analysis through IFAS and EFAS places Puncak Dunu in Quadrant I, indicating that an aggressive Strength–Opportunity strategy supported by a master plan is required for sustainable destination management.